Effects of Matricaria Chamomilla on the Severity of Nausea and Vomiting Due to Chemotherapy - fatemeh borhan; ali naji; Mehdi Molavi Vardanjnai; Lida Sasani (مراقبت پرستاری و مامایی ابن سینا, 2017)
Introduction: Uncontrollable nausea and vomiting can cause delay in chemotherapy and affects patient’s life. Since Matricaria chamomilla seems to be effective in reducing nausea and vomiting, this study aimed to determine the effect of its extract on the severity of nausea and vomiting due to chemotherapy. Methods: This quasi experimental study was conducted on the patients receiving chemotherapy in Chemotherapy Wards of Zahedan Tamin Ejtemaee Hospitals in 2015. In doing so, 60 patients were selected through convenience-sampling method and assigned into intervention and control groups. Two hours before chemotherapy, the intervention group was given Matricaria chamomilla extract while the control patients were given distilled water as placebo. Nausea rate was measured using Visual Analogue Scale (VAS) 0, 2, 6, and 12 hours after chemotherapy. Results: In the beginning, there was no significant difference between the mean scores of nausea of two groups (P=0.4); however, 2 hours after the chemotherapy, nausea score increased in both groups and it was significantly higher in the control group. (P=0.034). After 6 and 12 hours, the mean scores of nausea in both groups declined; however, the control patients’ mean score was constantly and significantly higher. There was no significant difference between the two groups concerning vomiting (P>0.05). Conclusion: The results indicated that consuming Matricaria chamomilla extract can reduce nausea due to chemotherapy while it has no effect on vomiting.